Answer:
The average cost function is [tex]\bar C(x)=-\frac{1200}{x}+34[/tex].
The cost function is [tex]C(x)=-1200+34x[/tex].
The fixed costs are -$1200.
Step-by-step explanation:
If [tex]y = C(x)[/tex] is the total cost of producing x items, then the average cost, or cost per unit, is [tex]\bar C(x)=\frac{C(x)}{x}[/tex] and the marginal average cost is [tex]\bar C'(x)=\frac{d}{dx}\bar C(x)[/tex].
We know that the marginal average cost is given by
[tex]\bar C'(x)=\frac{1200}{x^2}[/tex]
[tex]\bar C'(x)=\frac{1200}{x^2}\\\\\bar C(x)=\int {\frac{1200}{x^2}} \, dx[/tex]
[tex]\mathrm{Take\:the\:constant\:out}:\quad \int a\cdot f\left(x\right)dx=a\cdot \int f\left(x\right)dx\\\\1200\cdot \int \frac{1}{x^2}dx\\\\\mathrm{Apply\:the\:Power\:Rule}:\quad \int x^adx=\frac{x^{a+1}}{a+1},\:\quad \:a\ne -1\\\\1200\cdot \frac{x^{-2+1}}{-2+1}\\\\-\frac{1200}{x}\\\\\mathrm{Add\:a\:constant\:to\:the\:solution}\\\\-\frac{1200}{x}+C[/tex]
Because [tex]\bar C(100)=22[/tex] C is
[tex]22=-\frac{1200}{100}+C\\C=34[/tex]
And the average cost function is
[tex]\bar C(x)=-\frac{1200}{x}+34[/tex]
[tex]x\cdot \bar C(x)=C(x)\\\\C(x)=(-\frac{1200}{x}+34)\cdot x\\\\C(x)=-1200+34x[/tex]
Cost functions are express as
[tex]C=(fixed \:costs)+(variable \:costs)\\C=a+bx[/tex]
According with this definition and the cost function that we have the fixed costs are -$1200.